On the elephant in the room: toward a generative politics of place on race in academic discourse. Issue 8 (13th September 2016) - Ulysse, Baudelaire; Berry, Theodorea Regina; Jupp, James C.
Abstract: In our conceptual essay, we draw on an exchange between a White scholar and a group of panelists on Critical Race Theory at an international conference. Taking up this exchange as our point of departure, we work in dialectical and multidimensional ways between the essentialized politics of place on race and critical anti-essentializing foundations in recent Critical Race Feminism and Critical White Studies' literatures. Working the dialectics and multidimensionality of the place that race makes in academic discourse, we recognize and ethically work through the essentialized politics of place in advancing anti-essentializing understandings of race. In articulating these anti-essentializing understandings, our conceptual essay drives at the notion of a generative politics of place on race in academic discourse. A generative politics of place holds essentialized realities and anti-essentializing foundations of race in dialectical and multidimensional tension for teaching, learning, and discussing race in local, national, and international contexts.